Immobilization of Sulfur from Different Precursors on Mini Rice-Husk-Ash Pellet Coated Chitosan Film and the Application for Mercury Vapor Uptake - Muhammad Adlim; Fitri Zarlaida; Ibnu Khaldun; Rizka Dewi; Sofyatuddin Karina; Ahmad Fairuz Omar (Indonesian Journal of Chemistry, 2019)
Stabilizing elemental mercury using elemental sulfur has been a laboratory standard method but the studies in gas system are still growing. This study aims to explore the effect of different type immobilized sulfurs toward the mercury vapor uptake in a mini gas reactor. Sulfur powder, sulfur dissolved in carbon disulfide and colloidal sulfur from sodium thiosulfate-hydrochloric acid were immobilized on mini rice-husk-ash pellets that were previously coated with chitosan film. The average thinness of chitosan film was 58 µm covered the each pellet surface with dimension of 3 mm Ø x 4 mm. The trends of the mercury uptake and the rate of absorption were described as follow; Pellet-Scolloid > Pellet-SCS2 > Pellet-Spowder. The mean percentages of mercury uptake after 1 h running at 70oC were 99.36; 89.09 and 75.00 respectively. The reverse trends were observed for the size of S-particle aggregation and the amount of S found on the pellet surface.